Equation for determining the homeostatic model of insulin-resistance: binational study - Guevara Tirado, Alberto (2025)
Introduction: The evaluation of the homeostatic model gives results close to the gold standard (hyperinsulinemic-euglycemic clamp). Objective: To develop an equation to determine the homeostatic model of insulin resistance. Material and methods: Analytical and cross-sectional study of secondary databases of 2004 Venezuelan adults and another of 4363 Mexicans. The variables were: homeostatic model of insulin resistance (HOMA-2), basal insulin, basal glucose. Multiple linear regression, scatter plot, and student t test were used. Results: The regression equation was -0.694+(0.138*basal insulin)+(0.009*basal glucose), where HOMA2-IR increases 0.138 for each U/mL of insulin and increases 0.009 for each mg/dL of basal glucose. The R2 value was 0.983 (Venezuelan database), indicating that 98% of the change in HOMA2-IR can be explained by the model based on basal insulin and glucose. The equation was applied to the Mexican adult database (n=4363), obtaining a coefficient of determination R2 of 0.897, implying that 90% of the variation in HOMA2-IR from the clinical calculator can be explained by HOMA2-IR from the regression equation. With a HOMA2-IR cut-off point of 2, lipid, glycemia, insulinemia, waist circumference, BMI, and blood pressure values were higher in the presence of HOMA2-IR levels ≥2 in the Venezuelan and Mexican databases. Conclusions: The regression equation to determine HOMA2-IR based on basal insulin and glucose is close to the HOMA2-IR clinical calculator.